Phone alert system - Rayapati, Anisha (Kansas State University, 2015)
There has been vast growth in development of mobile applications over the past few years. Many competitors in this area are involved in research and development on new platforms and user experience. One such technology is Android, whose credit goes to the Internet giant Google. Android supports a variety of mobile phones and tablets many manufactured by distinguished companies. These phones are described as next generation mobiles [as described by Google]. Android, being open source and free to use platform, offers the developers a broad way to build different kind of applications. Currently, if a user leaves his/her mobile at home or some other place, there is no option for him/her to see the messages or missed calls until they get back home. To avoid such things, I have built an Android application where we can integrate the mobile phone with SMTP (Simple Mail Transfer Protocol) email system so that the user will get the notification of email or SMS to their email client which is installed on his/her workstation. It will also allow the user to set the profile of the phone as Silent, Ring or Vibrate just by sending messages to the phone. The developed Android software allows users to start the app and give the desired email to which the notifications are to be sent. It will also allow saving the timings during which we need the notifications. The days on which the same notification alert is required can also be mentioned through the app. This will help users to track their mobile by changing its mode to ring just by sending a message.
Keywords: Android; UML; Testing; Computer Science (0984)